Insulin dysregulation in horses with induced obesity - Rodrigo M. Ribeiro; Debora S.F. Ribeiro; Cahuê Francisco R. Paz; Alexandre A.O. Gobesso; Rafael R. Faleiros (Pesquisa Veterinária Brasileira, 2020)
ABSTRACT: Insulin deregulation (ID) is a central player in the pathophysiology of equine metabolic syndrome (EMS), which is associated with generalized and/or regional obesity. The objective of this experiment was to characterize the alterations in the hormonal profile in horses exposed to a hypercaloric diet. A total of nine Mangalarga Marchador adult horses with initial body condition score (BCS) of 2.9±1/9 (mean±SD) were submitted to a high calorie grain-rich diet for 5 months. The data was collected before the start of the experiment and every 15 days until the end of the experiment and glucose and insulin concentrations were measured in the plasma. Proxies G:I, RISQI, HOMA-IR and MIRG were calculated. The low-dose oral glucose tolerance test (OGTT) was performed and the total area under the glucose (GTA) and insulin (ITA) curves at three different timepoints (before inducing obesity, after 90 days and after 150 days) was used. Analysis of variance of the results was performed considering the time effects and the means were compared with repeated measures by the Tukey’s test (P≤0.05). The ID was observed during the first 90 days of the experiment and was characterized as a decompensated ID, showing an increase of basal glucose and insulin plasma levels, changes in all proxies and a significant increase in GTA (P<0.001) and ITA (P<0.05). However, a clear compensation of the ID was evident after 150 days of experiment, which was supported by data from the insulin secretory response of β cells of the pancreas that showed an increase in insulin plasma levels, after fasting or exposure to gastric glucose, with a concomitant decrease in fasting glucose and fructosamine levels, and a decrease of GTA and marked increase of ITA (P<0.0001) in the dynamic test. These findings confirm the occurrence of hyperinsulinemia associated with insulin deregulation in Mangalarga Marchador horses exposed to hypercaloric diets.